Rights of the Ethnic Minorities under International Law: A Legal Monograph on Bangladesh and South Asia - Haque, Md. Tanzimul; Haque, Zeba Farah (Kathmandu School of Law Review, 2019)
The fact that the indigenous people have always been subject to oppression and discrimination is undeniable. It is very unlikely, especially in the South Asian region, to see proper implementation of the laws that uphold the rights of ethnic minorities. Starting from political freedom and cultural practices to education and economic rights, these people are subject to denial of access in different sectors. This paper aims at exploring those loopholes in the legal systems which are the compounding factors of such deprivation. Mostly focusing on the legal frameworks of the South Asian countries regarding rights of minorities, especially Bangladesh, this paper shall also include a comparison between the provisions of the national as well as international laws that enshrine the rights of different ethnic minorities. In addition to that, this paper shall also address the insufficiency of existing national and international obligations and try to look for answers on whether these are enough to protect minority rights or not. Moreover, the researchers equally emphasize on the necessity of international human rights law perspective in this particular field. Divided into several chapters, this paper stratifies the national laws, international instruments, eventually knitting into a comparison among South Asian countries like Bangladesh, India, Pakistan, and Nepal regarding the current context rights of indigenous people. The paper shall further argue the failure of government versus lack of susceptibility in this platform. Besides, through this research paper, how these rights can be administered and effectively enforced shall also be brought to light along with some recommendations. To recapitulate, by the end of this paper, this proposition should be well understood as to how the indigenous people have always suffered, what legal remedies they can seek if their rights are infringed, and what the government and international community can do in order to execute and validate these rights.